Developing a National Minimum Data Set for Kawasaki Disease Registry in Iran - Qazizadeh, Zainab; Shahbaznejad, Leila; Navaeifar, Mohammad Reza; Rezai, Mohammad Sadegh (Frontiers in Pediatrics, 2022)
Background: Kawasaki Disease is an acute and self-limited systemic inflammatory and febrile illness, which is the most common cause of acquired heart disease in children in developed countries. The incidence of KD in Asian countries is high. But, data is not available from the Middle East. So, the aim of this study was to develop an MDS to set up a national registry for KD to estimate the burden of disease in Iran. Materials and Methods: This cross-sectional and descriptive study was conducted in 2020. Literature review, data collection from patients҆ medical records, and expert panel approach were used to design this MDS. Data elements with a Content Validity Ratio (CVR) of more than 0.56 were selected as the MDS of the registry. Results: Overall, 99 data elements were recognized. Of which, 51 and 48 data elements were verified and rejected, respectively. Moreover, 17 data elements were added as required by experts. Eventually, 68 data elements were chosen as the MDS of the national KD registry of IRAN; of which, 17 and 51 data elements were classified as administrative and clinical data, respectively. Conclusions: These precise, integrated, and comprehensive developed data elements and the national KD registry will lead to effective disease management and thus, improve the quality of care and, consequently, improve public health.